CO2 methanation on transition-metal-promoted Ni-Al catalysts: Sulfur poisoning and the role of CO2 adsorption capacity for catalyst activity. Issue 36 (February 2020) - Wolf, Moritz; Wong, Ling Hui; Schüler, Christian; Hinrichsen, Olaf
Highlights: A unique combination of in situ and ex situ sulfur poisoning techniques discloses new aspects of CO2 methanation on Ni-Al catalysts promoted by Mn, Fe, Co, Cu and Zn. Promoted Ni-Al catalysts show a superior resistance in CO2 methanation versus in situ H2 S poisoning when compared to the non-promoted benchmark. A novel method to distinguish different CO2 adsorption sites on promoted Ni-Al catalysts is presented. Mn- and Fe-doped samples show the highest activity and also the highest CO2 adsorption capacity (related to Ni 0 and the promoter phase). Cu causes severe catalyst deactivation by adsorbing CO2 and converting it to CO. Abstract: Co-precipitated and promoted Ni-Al catalysts, specifically Mn- and Fe-doped systems, rank among the most active and thermostable catalysts for the CO2 methanation reaction. However, little is known about the resistance of those catalysts against sulfur poisoning and the exact reasons for activity enhancement. In order to resolve these questions, a co- precipitated Ni-Al benchmark catalyst with a Ni loading of 41 wt% was promoted by up to 5 wt% of Mn, Fe, Co, Cu and Zn. CO2 methanation activity and stability against sulfur poisoning was evaluated by in situ poisoning with 5 ppm of H2 S and ex situ poisoning with liquid (NH4 )2 S. Characterization results obtained from XRD, TPR, N2 physisorption, H2 and CO2 chemisorption contributed to derive structure- activity relationships. All promoted samples show a superior resistance versus H2 S poisoning, which is correlated to H2 S adsorption on promoter phases, protecting active Ni sites. Based on the adsorption properties of spent in situ poisoned samples, the individual CO2 uptake of the Ni 0 and the promoter phase were identified and correlated to CO2 methanation activities of ex situ poisoned samples. Enhanced activities of Mn- and Fe-doped samples are ascribed to CO2 adsorption on promoter phases and subsequent conversion to CH4 . In contrast, CO2 adsorbed on Cu is converted to CO, causing severe catalyst deactivation. Regarding activity, Co and Zn have insignificant impact. Apparent activation energies of all samples are similar and in the range of 81–92 kJ/mol. Sulfur poisoning and promoter-induced activity changes are therefore ascribed to structural rather than electronic effects for the investigated promoter loadings.